Koordinasi Sistem Proteksi Trafo Distribusi 20 KV (Studi Lapangan PT. PLN Persero Unit Lamongan) - Rohmat Syaifuddin; Zainal Abidin; Affan Bachri (Jurnal Teknika, 2020)
Electricity distribution systems that use aerial or ground wires often experience various disturbances. Disturbances that often occur are symmetry disturbances or asymmetric disturbances which can be in the form of a short circuit of one phase to the ground, between phases or the breakup of one or more. To determine the magnitude of the fault current is needed transformer distribution system analysis to determine the disturbances that will occur. The transformer which is the main equipment in a GI must be considered to get the right current and safety circuit. Designing an appropriate transformer setting is an effort to protect equipment, systems and consumer needs from interference that may occur in the distribution system. Calculation of the fault current and the magnitude of the transformer nominal current will be used as an important reference in determining the transformer setting in the distribution of voltage to consumers. From the results of these calculations, it can be concluded that the relay feeder performance time is slower than the relay time in the calculation. The data in the field is still in a suitable condition (the difference is not too far away), so that the overall OCR - GFR settings in the field are still in good condition.